Prevalence and Clinico- Laboratory Profile of Tuberculosis in Children in Nobel Medical College, Biratnagar - Sah, Vijay Kumar; Giri, Arun; Niraula, Niraj (Journal of Nepalgunj Medical College, 2019)
Introduction: Tuberculosis infection is very common, and it continues to be the major public health problem in Nepal. Published data about the epidemiology of TB in children is scarce in Nepal, though it is considered one of the most common causes of childhood morbidity in the country. Aims and objectives: To calculate the prevalence of tuberculosis in children aged 0-15 years and to study their clinico-laboratory profile. Methodology: This is a hospital based study conducted in Nobel Medical College Teaching Hospital, Biratnagar over a period of one year. We analyzed 289 children aged 0-15 years suspected of having tuberculosis on clinical grounds and subjected to further screening tests. Results: Majority of the children were males and most of the children were 5-15 years of age. 15 of the cases were diagnosed as tuberculosis out of which one case was bacteriologically confirmed pulmonary tuberculosis and be 5.2 %. Fever and cough were the most common clinical presentations and mantoux test and chest X-ray were most suggestive in majority of the cases. Conclusions: This study supports the use of history and thorough clinical examination and high index of clinical suspicion for diagnosis of childhood tuberculosis.